Screening of Psychiatric Disorder on Plastic Surgery Patients - Angeline Fenisenda (HM Publisher, 2021)
Psychiatric disorders can be found pre-existing in people who seek plastic surgery or due to unsatisfied results. This literature review aimed to describe the screening of psychiatric disorders in plastic surgery patients. Using a preoperative assessment tool to identify patients with underlying psychiatric issues, inappropriate motivations, or unrealistic expectations, as well as to provide a reason for psychological referral, may help avoid such situations. Such a tool would not replace formal in-depth assessment but would alert the medical team of needing further evaluation and possible psychological consultation. Body dysmorphic disorder (BDD) is under-detected in patients presenting for cosmetic surgery, and patients with BDD are highly likely to seek cosmetic surgery. Valid and valuable screening and diagnostic instruments for BDD are available. A simple screening questionnaire (BDDQ) should be used, followed by administration of the BDD SCID for a fraction of patients with a BDDQ-positive screen result to be valuable tools to identify these patients. In conclusion, there was variable psychiatric screenings prior plastic procedure. Some adaptational screening methods will help if there is no proper guideline in the country.